Learning Media Applications and Introduction of Javanese Gamelan Musical Instruments Based on Android - Muchammad Sofyan Ariefbillah; Cindy Taurusta (Procedia of Engineering and Life Science, 2021)
The role of technology, especially information technology, is very helpful in people's lives, from the aspects of education, business, to the health sector. In this day and age, many modern musical instruments have begun to shift the existence of traditional music, especially this typical Javanese musical instrument, namely Gamelan. With the development of the times, the public's interest in this traditional Gamelan instrument is decreasing. So that this application has a problem formulation, namely how to design and create an android application that concerns the introduction and learning of various types of gamelan musical instruments. This study aims to produce an application for the introduction of an Android-based gamelan instrument that can be used by all groups to be more familiar with and interested in learning and preserving gamelan instruments. This research was conducted with a survey method to obtain data or opinions to test this application. Based on the research that has been done, a conclusion can be drawn with this research which results in an application that can help and make it easier for people to know the various types of Javanese gamelan.